Studiefonds van Het Mangkoenagara VII :1924-1930 - Tasya Kaliyana Sanjani; Eka Yudha Wibowo (Keraton: Journal of History Education and Culture, 2025)
This study examines the implementation of Studiefonds Van Het Mangkoenagoro VII (1924-1930) as a concrete manifestation of the Ethical Political Trilogy, especially in the field of education in Praja Mangkunegaran. This research aims to: (1) analyze the distribution mechanism and implementation of Studiefonds, (2) evaluate the role of Mangkunegara VII in the management of the education fund, and (3) identify the impact on the Sentana and Abdi Dalem. The method used the historical method with the stages of heuristics (Mangkunegaran archives, Studiefonds annual report), source criticism, interpretation, and historiography. The results showed that Studiefonds was divided into two types: Studiefonds A (funds from the Praja treasury) and Studiefonds B (funds from previous recipient installments). This policy succeeded in increasing access to modern education for bumiputera, although it was limited to the Praja elite. Significant impacts included: (1) the birth of educated personnel for colonial and Praja administrative needs, (2) the emergence of a new social class of educated people. Mangkunegara VII's role was reflected in the establishment of the Commissie van Advies to oversee the distribution of funds and the expansion of Mangkunegaran schools. The novelty of this research lies in finding that Studiefonds became a unique model of community-based education funding in the colonial era, as well as a reflection of the spirit of limited autonomy of Praja Mangkunegaran. The economic crisis of 1930 was a factor in the decline of the program's effectiveness.